2020
DOI: 10.36941/jesr-2020-0096
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Significance of Process on Effectiveness of Teacher Evaluation in Kwekwe Schools of Zimbabwe

Abstract: Zimbabwe adopted Results Based Management (RBM) in order to evaluate the performance of its workers. For the process to be ‘significant’ and meet the basic attribute of utility, evaluation information should be focused towards predetermined uses. The objective of this study was to assess the significance of the teacher performance evaluation process and examine the relationship between the significance and the effectiveness of the evaluation system of Kwekwe district in Zimbabwe. The study was situated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Outstanding teachers were not rewarded, or poorly performing teachers were punished based on evaluation results. This process has negatively impacted teachers' motivation and attitudes (Musodza, et al, 2020), and global competitiveness and high-stakes accountability practices have steadily weakened teachers' expertise, authority, and professionalism by restricting teachers' ability to exercise professional discretion (Amrein-Beardsley, 2020). The study (Jerrim, J., & Sims, S. 2021) showed that there is a cross-national relationship between the accountability of the school system and the extent to which school employees feel stressed and stressed about this aspect of their job, although increasing accountability may lead to short-term improvements in Student performance, but this may be counterproductive in the long term if it leads to a reduced supply of teachers, with the shortage of high-quality teachers failing to keep up with demand, as a study (Camphuijsen, et al, 2022) reported that teachers suffer from The severe stress and depression caused by accountability control measures, and the effect of accountability measures on reinforcing unwanted emotional norms.…”
Section: Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Outstanding teachers were not rewarded, or poorly performing teachers were punished based on evaluation results. This process has negatively impacted teachers' motivation and attitudes (Musodza, et al, 2020), and global competitiveness and high-stakes accountability practices have steadily weakened teachers' expertise, authority, and professionalism by restricting teachers' ability to exercise professional discretion (Amrein-Beardsley, 2020). The study (Jerrim, J., & Sims, S. 2021) showed that there is a cross-national relationship between the accountability of the school system and the extent to which school employees feel stressed and stressed about this aspect of their job, although increasing accountability may lead to short-term improvements in Student performance, but this may be counterproductive in the long term if it leads to a reduced supply of teachers, with the shortage of high-quality teachers failing to keep up with demand, as a study (Camphuijsen, et al, 2022) reported that teachers suffer from The severe stress and depression caused by accountability control measures, and the effect of accountability measures on reinforcing unwanted emotional norms.…”
Section: Study Resultsmentioning
confidence: 99%
“…Two studies were also conducted in Turkey (Cobanoglu et al, 2018) & (Aslantas, 2020), as well as two studies in Iran (Kashmiri, 2021) & (Franchi & Rashidi, 2022). There is one study each: Ireland (Ball, 2016), Sweden (Christian, 2017), Kenya (Piper, et al, 2018), Zimbabwe (Musodza, et al, 2020), and Indonesia (Suriagiri, et al, 2022). At a rate of (3.44%) for each study, separately out of the total number of previous studies.…”
Section: Study Resultsmentioning
confidence: 99%
See 1 more Smart Citation